Effect of cover crops on pluvial flooding: a modelling study in agricultural lowland hill in Slovakia - Ševčík, Michal; Petluš, Peter; Petlušová, Viera (Frontiers in Agronomy, 2026)
IntroductionWe assessed the impact of cover crops on surface runoff in Belá, a pluvial-flood–threatened area in southwestern Slovakia with a relatively low slope.MethodsUsing the 2D unsteady-flow HEC-RAS model, we simulated four cropping scenarios (real, proposed, optimum, and pessimum) under a synthetic design storm with a 10-year return period.ResultsScenarios incorporating cover crops (optimum and proposed) substantially reduced cumulative runoff volume. The pessimum (bare-soil) scenario produced 9.54 times higher cumulative runoff volume than the optimum scenario during the simulated event. Cover-crop scenarios also delayed peak flows by 70–130 minutes during periods of high crop or cover-crop coverage.Discussion/ConclusionsThe reductions and delays are attributed to improved infiltration capacity and increased surface roughness associated with continuous vegetative cover. In contrast, bare soil generated rapid, high-volume runoff, indicating high vulnerability to flash floods. Overall, continuous vegetative cover can mitigate intense rainfall impacts, and our findings provide practical recommendations for sustainable agricultural management supporting climate-change adaptation.